Increased levels of deleted in malignant brain tumours 1 (DMBT1) in active bacteria-related appendicitis - Kämmerer-Gaßler, Elke; Renner, Marcus (Histopathology, 2012)
Kaemmerer E, Schneider U, Klaus C, Plum P, Reinartz A, Adolf M, Renner M, Wolfs T G A M, Kramer B W, Wagner N, Mollenhauer J & Gassler N (2012) Histopathology 60, 561-569 Increased levels of deleted in malignant brain tumours 1 (DMBT1) in active bacteria-related appendicitis Aims: Deleted in malignant brain tumours 1 (DMBT1; gp340) is a secreted glycoprotein which is found in the surface lining epithelia of human small and large intestine. DMBT1 is suggested to play a role in enterocyte differentiation and surface protection from intestinal bacteria. The aim of this study was to elucidate DMBT1 expression in bacteria-related active intestinal inflammation such as appendicitis. Methods and results: mRNA and protein levels of DMBT1 were analysed in surgical resections of 50 appendices (active inflammation: n = 25). In non-actively inflamed appendices, inter-individual differences in basal DMBT1 levels of enterocytes and some non-epithelial cells were found. In active appendicitis, enterocytic DMBT1 mRNA expression was increased approximately fivefold, which was paralleled by a corresponding increase of cytoplasmic and secreted DMBT1 protein levels. Increased DMBT1 expression was predominant in enterocytes adjacent to erosive lesions or ulcers. Conclusions: Our data demonstrate that bacteria-related active inflammation results in a sharp increase of DMBT1 levels in enterocytes. These findings substantiate the view that DMBT1 is of functional relevance for host defence and modulation of the course of intestinal bacteria-related inflammatory responses.